FDY crude oil type oil agent for polyester fiber and preparation method thereof
By adding modified wear-resistant agents to the FDY crude oil type oil agent, combined with the preparation methods of bundling agents, antistatic agents, etc., the existing FDY crude oil type oil agents have been solved, and a more stable spinning process and higher performance requirements have been achieved.
Patent Information
- Application Number
- CN202411308495.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-19
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-09-19
AI Technical Summary
The heat and wear resistance of the existing FDY crude oil agents is not ideal enough, resulting in the problems of wool and broken heads easily occur during the polyester spinning process.
The clustering agent, antistatic agent, emulsifier and smoothing agent are mixed in a specific mass ratio, and triethanolamine and modified wear-resistant agent are added. Through stirring and phacoemulsification and other processes, an FDY crude oil type oil agent with improved heat and wear resistance is prepared.
It improves the heat and wear resistance of FDY crude oil type oil agent, reduces the phenomenon of wool and head breaking during spinning, and the oil agent has good stability during storage and use, and is not easy to delaminate or break the milk.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of chemical materials, and in particular to an FDY crude oil type oil agent for polyester fiber and a preparation method thereof. Background Art
[0002] Polyester, also known as polyester fiber, is an important variety of synthetic fibers. Polyester is a fiber-forming polymer made from purified terephthalic acid (PTA) or dimethyl terephthalate (DMT) and ethylene glycol (MEG) through esterification or ester exchange and polycondensation. The fiber is made through spinning and post-treatment. Its biggest advantage is its good wrinkle resistance and shape retention.
[0003] FDY (Fully Drawn Yarn) crude oil for polyester spinning is a commonly used chemical fiber oil. It is widely used in mechanical spinning processes. It can significantly reduce lint and broken ends during high-speed spinning, bringing convenience to the spinning process, reducing costs and saving energy.
[0004] The quality requirements for FDY crude oil type oil generally include: the oil emulsion has fine particles, is stable and easy to prepare, has no stratification, and has no odor; it has good spinnability, no abnormal breakage, and a high rate of superior products under the same process conditions; it has good dyeing uniformity, good package forming, and no lint; the oil has good heat resistance, no obvious smoke, less hot roller coking, and excellent antistatic properties; it has good bundling properties and good winding forming; the fiber has uniform oil content, and textile users have good feedback.
[0005] The main component of FDY crude oil is surfactant, which is used to adjust the friction coefficient of the fiber, giving the fiber good smoothness, adhesion and antistatic properties. Its function is to adjust the friction between fibers and fibers, fibers and metals, improve the smoothness of the fiber surface and reduce the charge of the fiber; on the other hand, it increases the number of ions on the fiber surface, improves the hygroscopicity, and quickly dissipates the generated static electricity. In the high-speed spinning process, the oil can replace the air on the fiber surface in time to achieve complete wetting, play a good role in smoothness and antistatic properties, and reduce lint and broken ends in the high-speed spinning process.
[0006] Polyester has a high spinning speed and high heat resistance requirements, so FDY crude oil must have good smoothness and good heat resistance. In addition, in order to make the oil uniform and stable and the oiled fiber adapt to high-speed winding, other additives are added to the preparation of the oil, such as wear prevention agents, viscosity regulators, defoamers, preservatives, oil film enhancers, etc.
[0007] At present, the disadvantages of the FDY crude oil type oil in the prior art are that the heat resistance and wear resistance of the FDY crude oil type oil are not ideal. Summary of the invention
[0008] One of the problems solved by the present invention is how to provide an FDY crude oil type oil agent for polyester fiber with good heat resistance and wear resistance.
[0009] In order to solve at least one of the above problems, the present invention provides a method for preparing an FDY crude oil type oil agent for polyester fiber, the preparation method comprising:
[0010] S100, according to the mass ratio of sizing agent: antistatic agent: emulsifier: smoothing agent = (4-6): (5-8): (20-22): (55-60), add sizing agent, antistatic agent, emulsifier and smoothing agent into a reaction kettle, start stirring, raise the temperature to 40° C. to 50° C. and continue stirring for 20 min to 40 min to obtain a first mixture;
[0011] S200, according to the mass ratio of triethanolamine: anti-wear agent: first mixture = (3-6): (10-15): 100, put triethanolamine and anti-wear agent into the reaction kettle and mix with the first mixture, keep warm and continue stirring for 10 to 20 minutes to obtain FDY crude oil type oil agent;
[0012] The anti-wear agent is prepared by the following steps: preparing a composite inorganic filler including silicon dioxide and kaolin, mixing the composite inorganic filler with hydroxyethyl acrylate and ethylene glycol dimethacrylate, and adding dibenzoyl peroxide to react to obtain the anti-wear agent.
[0013] In any of the above technical solutions, the sizing agent includes at least one of lauroyl diethanolamine, coconut oleic acid diethanolamide, oleic acid triethanolamine, polyethylene glycol oleate, and polyethylene glycol laurate.
[0014] In any of the above technical solutions, the antistatic agent includes at least one of lauryl alcohol polyoxyethylene ether potassium phosphate, secondary alkyl sodium sulfonate, and lauryl alcohol polyoxyethylene ether.
[0015] In any of the above technical solutions, the emulsifier includes at least one of isomeric alcohol polyoxyethylene ether, sorbitan fatty acid ester, polyethylene glycol fatty acid ester, castor oil polyoxyethylene ether, cardanol polyoxyethylene ether, and sodium lauryl ether sulfate.
[0016] In any of the above technical solutions, the lubricant includes at least one of mineral oil, white oil, vegetable oil, silicone oil, and at least one of fatty alcohol oleate or polyol oleate.
[0017] In any of the above technical solutions, based on 100 parts by mass, the lubricant includes: 55 parts of mineral oil; 15 parts of polyol fatty acid ester; 10 parts of copolyether; 10 parts of phosphate ester; and 10 parts of silicon oxide.
[0018] In any of the above technical solutions, the antistatic agent is prepared by the following steps:
[0019] S110, dissolving chitosan in a 2% vol to 3% vol acetic acid aqueous solution to prepare a 4 wt % to 6 wt % chitosan aqueous solution;
[0020] S120. Mix the initiator, isotridecyl alcohol polyoxyethylene ether and chitosan aqueous solution in a mass ratio of initiator: water-soluble acrylic monomer: isotridecyl alcohol polyoxyethylene ether: chitosan aqueous solution = (4-6): (60-80): (40-50): 100, stir evenly at a temperature of 50°C to 55°C, raise the temperature to 75°C to 80°C, add the water-soluble acrylic monomer, continue stirring for 1h to 1.5h, and cool to room temperature after stirring to obtain an antistatic agent.
[0021] In any of the above technical solutions, the anti-wear agent is prepared by the following steps:
[0022] S311, mixing ethyl silicate with a mixture of ethanol and water, adding hydrochloric acid to adjust the pH value to 4 to 5, stirring and reacting for 2h to 3h, adding sodium hydroxide aqueous solution after the stirring to adjust the pH value to 11 to 12, standing for 10h to 12h to obtain silica sol, and immersing the silica sol in ethanol for aging for 24h to 36h, and taking it out to obtain silica gel;
[0023] S312, firstly mix Tween 60, paraffin, silica gel and carbon tetrachloride, then gradually add water and stir, control the system temperature to 50° C. to 60° C., perform ultrasonic emulsification under heat preservation conditions to obtain silica emulsion;
[0024] S313, feeding the silica emulsion into a reactor, using carbon dioxide as a medium, supercritically extracting the liquid phase in the silica emulsion, cooling and releasing the pressure after the supercritical extraction, filtering and washing the solids, and mixing the solids and water uniformly to obtain an aqueous phase mixed liquid including the silica core material;
[0025] S314, mixing Tween 60, kaolin, vegetable oil and water, raising the temperature to 65° C. to 70° C. and performing ultrasonic emulsification to obtain an oil phase mixed liquid including kaolin wall material;
[0026] S315, adding the oil phase mixture dropwise into the water phase mixture containing Tween 60, and after the addition is completed, ultrasonic emulsification is performed evenly to separate the solid matter, thereby preparing a composite inorganic filler.
[0027] S316, mixing the composite inorganic filler with hydroxyethyl acrylate and ethylene glycol dimethacrylate, adding dibenzoyl peroxide and polyethylene glycol with a molecular weight of 400 to 600, raising the temperature to 75°C to 80°C, stirring and reacting for 3 hours to 3.5 hours, to obtain an anti-wear agent.
[0028] In any of the above technical solutions, in S311, by mass ratio, ethyl silicate: ethanol: water = (6-10): (30-35): 100; in S312, by mass ratio, Tween 60: paraffin: silica gel: carbon tetrachloride: water = (4-8): (15-20): (30-40): 60: 100; in S313, by mass ratio, the supercritical extraction is carried out at a temperature of 30° C. to 33° C. and a pressure of 7.2 MPa to 7.5 MPa; in S314, by mass ratio, Tween 60: kaolin: vegetable oil: water = (4-8): (20-25): (40-50): 100; in S315, the mass ratio of Tween 60: oil phase mixture: water phase mixture = (4-8): (60-80): 100; in S316, the mass ratio of dibenzoyl peroxide: composite inorganic filler: hydroxyethyl acrylate: ethylene glycol dimethacrylate: polyethylene glycol = (0.2-0.3): (35-45): 100: 100: 150.
[0029] The present invention also provides an FDY crude oil type oil agent for polyester fiber, and the FDY crude oil type oil agent for polyester fiber is obtained by adopting the preparation method of any of the above technical solutions.
[0030] Beneficial Effects
[0031] The preparation method of the present invention firstly puts a sizing agent, an antistatic agent, an emulsifier and a smoothing agent into a reactor, starts stirring, heats up to 40°C to 50°C and continues stirring for 20min to 40min to obtain a first mixture; then puts triethanolamine and an anti-wear agent into the reactor and mixes with the first mixture, keeps the temperature and continues stirring for 10min to 20min to obtain an FDY crude oil type oil. The FDY crude oil type oil is mainly used in polyester production. As an indispensable auxiliary agent in the polyester spinning process, it can make the fiber have good smoothness, sizing and antistatic properties, thereby meeting the requirements of fiber processing. Among them, the anti-wear agent of the present invention includes silicon dioxide with excellent mechanical properties and kaolin with good heat resistance, and is polymer modified. The invention improves the dispersion stability of the anti-wear agent by modifying the anti-wear agent, thereby giving the FDY crude oil type oil agent good heat resistance and wear resistance by adding the improved anti-wear agent, and the FDY crude oil type oil agent can be stored stably for a long time, and is not easy to agglomerate, deteriorate and stratify during storage and use. DETAILED DESCRIPTION
[0032] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the following is a detailed description of the specific embodiments of the present invention.
[0033] Unless otherwise specified, the reagents and raw materials used in the present invention can be purchased through commercial channels. The experimental methods in the following examples without specifying specific conditions are selected according to conventional methods and conditions, or according to the product specifications.
[0034] FDY crude oil type oil is mainly used in polyester production. It is an essential auxiliary agent in the polyester spinning process to ensure that the polyester fiber has good smoothness, bundling and antistatic properties. Because polyester spinning speed is fast and the spinning temperature is high, FDY crude oil type oil must have good heat resistance. In addition, it is also necessary to give the fiber and fiber, as well as the fiber and other parts a suitable friction coefficient through FDY crude oil type oil.
[0035] For example, inorganic fillers such as titanium dioxide, silicon dioxide, calcium carbonate, zinc oxide, aluminum oxide, aluminum nitride, silicon carbide, and silicon carbide can be added to FDY crude oil. On the one hand, it can improve the thermal stability of FDY crude oil, and on the other hand, it can also improve the wear resistance of FDY crude oil.
[0036] However, due to the great differences in physical and chemical properties between inorganic fillers and commonly used raw materials such as sizing agents, antistatic agents, and smoothing agents, powdered or granular inorganic fillers are not stable in the FDY crude oil type oil system. If the particle size is too small, it is easy to agglomerate, and if the particle size is too large, it is easy to stratify. In addition, the FDY crude oil type oil itself is in the form of an emulsion, or it will be prepared into an emulsion after adding an appropriate amount of water. Since the water or other solvent components in the FDY crude oil type oil will evaporate under the conditions of hot roller drawing and extrusion and high temperature heating, it is easy to cause the oil film on the fiber surface to rupture. The rupture of the oil film will not only change the friction characteristics of the fiber, resulting in the problem of lint and broken ends, but will also further make it difficult to evenly distribute the inorganic filler. During long-term storage, the addition of inorganic fillers will also affect the storage stability of the emulsion, causing the FDY crude oil type oil to have the problem of emulsion instability during use, and stratification and demulsification during long-term storage or use. The premise for the use of inorganic fillers is that the problem of dispersion stability needs to be solved, and the addition of inorganic fillers is very necessary. Therefore, how to add inorganic fillers to FDY crude oil type oil in a suitable manner to improve the storage stability and thermal stability of FDY crude oil type oil is a technical problem that the following technical scheme is intended to solve.
[0037] The embodiment of the present invention provides a method for preparing an FDY crude oil type oil agent for polyester fiber, the preparation method comprising:
[0038] S100, according to the mass ratio of sizing agent: antistatic agent: emulsifier: smoothing agent = (4-6): (5-8): (20-22): (55-60), add sizing agent, antistatic agent, emulsifier and smoothing agent into a reaction kettle, start stirring, raise the temperature to 40° C. to 50° C. and continue stirring for 20 min to 40 min to obtain a first mixture;
[0039] S200, according to the mass ratio of triethanolamine: anti-wear agent: first mixture = (3-6): (10-15): 100, put triethanolamine and anti-wear agent into the reaction kettle and mix with the first mixture, keep warm and continue stirring for 10 to 20 minutes to obtain FDY crude oil type oil agent.
[0040] The purpose of the above steps is to prepare FDY crude oil type oil agent by uniformly mixing the raw materials. In order to achieve uniform mixing, the raw materials are fed into a reactor and stirred for a certain period of time under the condition of heating. Among them, the anti-wear agent is added last compared with other raw materials, and the anti-wear agent of the present invention is added after modification. The present invention improves the preparation process of inorganic fillers to prepare FDY crude oil type oil agent that can make the inorganic filler anti-wear agent uniformly and stably dispersed, thereby improving the thermal stability and wear resistance of the FDY crude oil type oil agent, and its performance is stable and good, it is not easy to stratify and demulsify during long-term storage, and it is not easy to have the problem of oil film rupture during use.
[0041] Before introducing the modification process of inorganic filler anti-wear agent, other raw materials used in the preparation process of FDY crude oil type oil are first explained. In the FDY crude oil type oil of the present invention, the sizing agent is a chemical auxiliary agent used in the fiber material processing process, and its main function is to improve the cohesion between fibers, so that the fibers can be bundled into bundles, thereby increasing the load-bearing capacity and tensile strength of the fibers. Exemplarily, the sizing agent used in the present invention includes at least one of lauroyl diethanolamine, coconut oil diethanolamide, oleic acid triethanolamine, polyethylene glycol oleate, and polyethylene glycol laurate.
[0042] An antistatic agent is a chemical substance that can increase the conductivity of the surface of an object and prevent static electricity accumulation. Its main function is to increase the conductivity of the material surface so that static charge can be leaked in time to avoid static electricity from affecting production. Exemplarily, the antistatic agent used in the present invention includes at least one of lauryl alcohol polyoxyethylene ether potassium phosphate, secondary alkyl sodium sulfonate, and lauryl alcohol polyoxyethylene ether.
[0043] Preferably, the antistatic agent of the present invention is prepared by the following steps:
[0044] S110, dissolving chitosan in a 2% vol to 3% vol acetic acid aqueous solution to prepare a 4 wt % to 6 wt % chitosan aqueous solution;
[0045] S120. Mix the initiator, isotridecyl alcohol polyoxyethylene ether and chitosan aqueous solution in a mass ratio of initiator: water-soluble acrylic monomer: isotridecyl alcohol polyoxyethylene ether: chitosan aqueous solution = (4-6): (60-80): (40-50): 100, stir evenly at a temperature of 50°C to 55°C, raise the temperature to 75°C to 80°C, add the water-soluble acrylic monomer, continue stirring for 1h to 1.5h, and cool to room temperature after stirring to obtain an antistatic agent.
[0046] More preferably, in terms of mass ratio, the initiator: water-soluble acrylic acid monomer: isomeric tridecanol polyoxyethylene ether: chitosan aqueous solution = 4:60:40:100.
[0047] The initiator can be specifically an ammonium persulfate (APS) initiator or a potassium persulfate (KPS) initiator. Isotridecyl alcohol polyoxyethylene ether is a condensation product of isotridecyl alcohol and ethylene oxide. As a nonionic surfactant, it can effectively mix the oil phase and the water phase to form a stable emulsion, increase the stability of the emulsion product, and prevent its stratification and precipitation.
[0048] An emulsifier is a surfactant that contains both a hydrophilic group and a lipophilic group in its molecule. Its main function is to reduce the interfacial tension of the components in the mixed system, form a relatively strong film or double electric layer on the surface of the droplets, prevent the droplets from aggregating with each other, and thus maintain a uniform emulsion. Exemplarily, the emulsifier used in the present invention includes at least one of isomeric alcohol polyoxyethylene ether, anhydrous sorbitan fatty acid ester, polyethylene glycol fatty acid ester, castor oil polyoxyethylene ether, cardanol polyoxyethylene ether, and sodium lauryl alcohol ether sulfate.
[0049] The smoothing agent can significantly improve the smoothness of the tow, making the surface of the tow smoother and more delicate, and also helps to reduce the friction coefficient between the tows, thereby reducing the entanglement and knotting of the tows during the production process. Exemplarily, the smoothing agent used in the present invention includes at least one of mineral oil, white oil, vegetable oil, silicone oil, and at least one of fatty alcohol oleate or polyol oleate. Preferably, based on 100 parts by mass, the smoothing agent of the present invention includes: 55 parts of mineral oil; 15 parts of polyol fatty acid ester; 10 parts of copolyether; 10 parts of phosphate ester; 10 parts of silicon oxide.
[0050] It should be noted that those skilled in the art are capable of selecting and adjusting the specific raw materials and component contents of the sizing agent, antistatic agent, emulsifier and smoothing agent according to actual needs. The selection of the above raw materials and components in the present invention is a preferred solution adapted to the anti-wear agent preparation process of the present invention. The anti-wear agent preparation process of the present invention will be described below.
[0051] The wear-resistant agent used in the present invention comprises silicon dioxide and kaolin and is subjected to polymer modification treatment. The wear-resistant agent used in the present invention is prepared by the following steps: preparing a composite inorganic filler comprising silicon dioxide and kaolin, mixing the composite inorganic filler with hydroxyethyl acrylate and ethylene glycol dimethacrylate, and adding dibenzoyl peroxide for reaction to obtain the wear-resistant agent.
[0052] Specifically, the wear-resistant agent used in the present invention is prepared by the following steps: first, an aqueous phase mixed liquid including a silica core material and an oil phase mixed liquid including a kaolin wall material are prepared, and a composite inorganic filler is prepared by dropping the oil phase mixed liquid into the aqueous phase mixed liquid; then, the composite inorganic filler is mixed with hydroxyethyl acrylate and ethylene glycol dimethacrylate, and dibenzoyl peroxide is added to react to obtain the wear-resistant agent.
[0053] Preferably, the anti-wear agent used in the present invention is prepared by the following steps:
[0054] S311, mixing ethyl silicate with a mixture of ethanol and water, adding hydrochloric acid to adjust the pH value to 4 to 5, stirring and reacting for 2h to 3h, adding sodium hydroxide aqueous solution after the stirring to adjust the pH value to 11 to 12, standing for 10h to 12h to obtain silica sol, and immersing the silica sol in ethanol for aging for 24h to 36h, and taking it out to obtain silica gel;
[0055] S312, firstly mix Tween 60, paraffin, silica gel and carbon tetrachloride, then gradually add water and stir, control the system temperature to 50° C. to 60° C., perform ultrasonic emulsification under heat preservation conditions to obtain silica emulsion;
[0056] S313, feeding the silica emulsion into a reactor, using carbon dioxide as a medium, supercritically extracting the liquid phase in the silica emulsion, cooling and releasing the pressure after the supercritical extraction, filtering and washing the solids, and mixing the solids and water uniformly to obtain an aqueous phase mixed liquid including the silica core material;
[0057] S314, mixing Tween 60, kaolin, vegetable oil and water, raising the temperature to 65° C. to 70° C. and performing ultrasonic emulsification to obtain an oil phase mixed liquid including kaolin wall material;
[0058] S315, adding the oil phase mixture dropwise into the water phase mixture containing Tween 60, and after the addition is completed, ultrasonic emulsification is performed evenly to separate the solid matter, thereby preparing a composite inorganic filler.
[0059] S316, mixing the composite inorganic filler with hydroxyethyl acrylate and ethylene glycol dimethacrylate, adding dibenzoyl peroxide and polyethylene glycol with a molecular weight of 400 to 600, raising the temperature to 75°C to 80°C, stirring and reacting for 3 hours to 3.5 hours, to obtain an anti-wear agent.
[0060] Further preferably, the anti-wear agent used in the present invention is prepared by the following steps:
[0061] S311. Ethyl silicate is mixed in a mixture of ethanol and water in a mass ratio of ethyl silicate: ethanol: water = (6-10): (30-35): 100, hydrochloric acid is added to adjust the pH value to 4 to 5, and the reaction is stirred for 2 h to 3 h. After the stirring is completed, sodium hydroxide aqueous solution is added to adjust the pH value to 11 to 12, and the mixture is allowed to stand for 10 h to 12 h to obtain a silica sol; the silica sol is immersed in ethanol and aged for 24 h to 36 h, and a silica gel is obtained after being taken out;
[0062] S312, firstly mix Tween 60, paraffin wax, silica gel, and carbon tetrachloride in a mass ratio of Tween 60: paraffin wax: silica gel: carbon tetrachloride: water = (4-8): (15-20): (30-40): 60: 100, then gradually add water and stir, control the system temperature to 50° C. to 60° C., and after all the water is added, perform ultrasonic emulsification under heat preservation conditions to obtain a silica emulsion;
[0063] S313, feeding the silica emulsion into a reactor, using carbon dioxide as a medium, supercritically extracting the liquid phase in the silica emulsion at a temperature of 30° C. to 33° C. and a pressure of 7.2 MPa to 7.5 MPa. After the supercritical extraction for 1.5 h to 2.5 h is completed, the temperature is lowered and the pressure is released, the solids are filtered and washed, and the solids and water are uniformly mixed at a mass ratio of solids: water = (30-40): 100 to obtain an aqueous phase mixed liquid including the silica core material;
[0064] S314, mixing Tween 60, kaolin, vegetable oil and water in a mass ratio of Tween 60: kaolin: vegetable oil: water = (4-8): (20-25): (40-50): 100, heating to 65° C. to 70° C. and ultrasonically emulsifying to obtain an oil phase mixed liquid including kaolin wall material;
[0065] S315, adding the oil phase mixture dropwise into the aqueous phase mixture containing Tween 60 in a mass ratio of Tween 60: oil phase mixture: aqueous phase mixture = (4-8): (60-80): 100, and after the dropwise addition, performing ultrasonic emulsification evenly to separate the solid matter, thereby preparing a composite inorganic filler.
[0066] S316. Mix the composite inorganic filler with hydroxyethyl acrylate and ethylene glycol dimethacrylate in a mass ratio of dibenzoyl peroxide: composite inorganic filler: hydroxyethyl acrylate: ethylene glycol dimethacrylate: polyethylene glycol = (0.2-0.3): (35-45): 100: 100: 150, add dibenzoyl peroxide and polyethylene glycol with a molecular weight of 400 to 600, raise the temperature to 75°C to 80°C, carry out stirring reaction for 3h to 3.5h, and obtain an anti-wear agent.
[0067] Silicon dioxide has the characteristics of high mechanical strength, good thermal stability and wear resistance, and kaolin is heat-resistant and chemically stable. Both are suitable for being used as inorganic fillers and added to the FDY crude oil type oil system. Considering that the dispersion stability of the powder or particles of the inorganic filler in the FDY crude oil type oil system is not good, the present invention performs the above improvement treatment on the inorganic filler based on silicon dioxide and kaolin.
[0068] The present invention prepares nano silicon dioxide by a sol-gel method. In addition, the present invention imparts a hydrophobic porous structure to the nano silicon dioxide by supercritical drying extraction. After preparing silicon dioxide gel by using ethyl silicate as a silicon source precursor, the present invention mixes paraffin wax, carbon tetrachloride and silicon dioxide gel, adds an emulsifier and water, and prepares a silicon dioxide emulsion, in which paraffin wax as a phase change material is uniformly mixed with silicon dioxide. In the subsequent supercritical drying, carbon dioxide is used as an extraction medium to extract the carbon tetrachloride organic solvent in the silicon dioxide emulsion under supercritical conditions, so that the silicon dioxide has a porous structure, and the paraffin wax is filled and attached to the porous silicon dioxide. Furthermore, by mixing the silicon dioxide filled and attached with paraffin wax in the porous structure with water, an aqueous phase mixed liquid including a silicon dioxide core material can be obtained. Since the pores of the silicon dioxide obtained by the present invention are filled with paraffin wax, after it is added to the FDY crude oil type oil agent system, the stability of the FDY crude oil type oil agent during use can be improved, so that it is not easy to demulsify.
[0069] Specifically, the temperature of FDY crude oil type oil increases during use. Usually, temperature changes will cause the properties and state of the emulsion to be unstable. When the temperature of the emulsion increases, the inorganic filler is first prone to stratification and sedimentation problems. By filling paraffin as a phase change material in the pores of silica, when the temperature of the emulsion-like FDY crude oil type oil increases, the liquefaction of paraffin can regulate the temperature on the one hand, and on the other hand, it also protects the silica. The liquefied waxy substance is coated on the surface and pores of silica, which can effectively prevent the silica from stratification and sedimentation problems. Furthermore, it is also necessary to coat the silica filled with paraffin in the pores. For this reason, the present invention uses a microcapsule structure, uses the silica filled with paraffin in the pores as the core material, and obtains microcapsules in an oil-in-water manner through an oil phase mixed liquid containing kaolin wall material. In other words, the composite inorganic filler of the present invention is a composite inorganic filler with porous silica loaded with paraffin as a core material and a kaolin coating layer as a protective wall material, which can maintain good stability and dispersibility in an organic polymer at high temperature. Finally, the present invention uses dibenzoyl peroxide as an initiator and performs polymer modification on the composite inorganic filler through a polymerization reaction of hydroxyethyl acrylate and ethylene glycol dimethacrylate to reduce its surface energy and further improve its stability and dispersibility in the organic polymer.
[0070] In this embodiment, wear-resistant agent samples 1-4 were prepared. The components of wear-resistant agent samples 1-4 are shown in Table 1. The specific preparation process is as follows:
[0071] S1, mixing ethyl silicate in a mixture of ethanol and water, adding hydrochloric acid to adjust the pH value to 4 to 5, stirring and reacting for 2 hours, adding sodium hydroxide aqueous solution after the stirring to adjust the pH value to 11 to 12, standing for 10 hours to obtain silica sol, and immersing the silica sol in anhydrous ethanol for aging for 24 hours, and taking it out to obtain silica gel;
[0072] S2. First, mix Tween 60, paraffin, silica gel and carbon tetrachloride evenly, then gradually add water and stir. During the process of adding water, control the system temperature to 55°C (the temperature error is controlled within 2°C), perform ultrasonic emulsification for 20 minutes at a power of 500W under heat preservation conditions to obtain a silica emulsion;
[0073] S3, sending the silica emulsion into a reactor, first evacuating the vacuum, and then using carbon dioxide as a medium to supercritically extract the liquid phase in the silica emulsion at a temperature between 30° C. and 33° C. and a pressure between 7.2 MPa and 7.5 MPa, and keeping the temperature and pressure for 2 hours. After the supercritical extraction is completed, the temperature is reduced and the pressure is released, and the solids are filtered and washed with water twice, and the solids and water are evenly mixed at a mass ratio of solids: water = 35: 100 to obtain an aqueous phase mixed liquid including the silica core material;
[0074] S4, mixing Tween 60, kaolin, vegetable oil and water, raising the temperature to 68°C (temperature error controlled within 2°C) and performing ultrasonic emulsification for 20 minutes at a power of 500 W to obtain an oil phase mixed liquid including kaolin wall material;
[0075] S5. The oil phase mixture is added dropwise into the aqueous phase mixture containing Tween 60 at a mass ratio of Tween 60: oil phase mixture: aqueous phase mixture = 6:65:100. After the addition is completed, ultrasonic emulsification is performed at a power of 500 W for 20 minutes to separate the solids and prepare a composite inorganic filler.
[0076] S6. Mix the composite inorganic filler with hydroxyethyl acrylate and ethylene glycol dimethacrylate, add dibenzoyl peroxide and polyethylene glycol with a molecular weight of 500, raise the temperature to 78°C (the temperature error is controlled within 2°C), stir and react for 3 hours to obtain an anti-wear agent.
[0077] Table 1
[0078]
[0079] In this embodiment, an antistatic agent is prepared, and its specific preparation process is as follows:
[0080] S1, dissolving chitosan in a 3% vol acetic acid aqueous solution to prepare a 6 wt % chitosan aqueous solution;
[0081] S2. According to the mass ratio of initiator: water-soluble acrylic acid monomer: isotridecyl alcohol polyoxyethylene ether: chitosan aqueous solution = 4:60:40:100, the initiator, isotridecyl alcohol polyoxyethylene ether and chitosan aqueous solution are mixed evenly, stirred evenly at 52°C (the temperature error is controlled within 2°C), heated to 78°C (the temperature error is controlled within 2°C), added with water-soluble acrylic acid monomer, and continued stirring for 1.5 hours. After stirring, it was cooled to room temperature to obtain an antistatic agent.
[0082] Example 3
[0083] In this embodiment, FDY crude oil type oil samples 1-4 are prepared. The FDY crude oil type oil samples 1-4 respectively use the corresponding anti-wear agent samples 1-4 as anti-wear agents, and use the antistatic agent of Example 1. The specific preparation process is as follows:
[0084] S100, according to the mass ratio of sizing agent: antistatic agent: emulsifier: smoothing agent = 4:6:20:55, lauryl diethanolamine sizing agent, antistatic agent, polyethylene glycol fatty acid ester emulsifier and smoothing agent are added into the reaction kettle, after stirring, the temperature is raised to 45°C (the temperature error is controlled within 2°C) and stirring is continued for 40 minutes to obtain a first mixture; wherein, based on the total amount of the smoothing agent being 100 parts by mass, the smoothing agent includes: 55 parts of mineral oil; 15 parts of polyol fatty acid ester; 10 parts of copolyether; 10 parts of phosphate ester; and 10 parts of silicon oxide;
[0085] S200, according to the mass ratio of triethanolamine: anti-wear agent: first mixture = 3:15:100, put triethanolamine and anti-wear agent into the reaction kettle and mix with the first mixture, keep warm and continue stirring for 15 minutes to obtain FDY crude oil type oil agent.
[0086] Comparative Example 1
[0087] In this comparative example, FDY crude oil type oil sample 5 was prepared. The specific preparation process of FDY crude oil type oil sample 5 was the same as that of Example 3, except that the anti-wear agent used was prepared by the following process:
[0088] S1. Ethyl silicate is mixed in a mixture of ethanol and water in a mass ratio of ethyl silicate: ethanol: water = 6:35:100, hydrochloric acid is added to adjust the pH value to 4 to 5, and the reaction is stirred for 2 hours. After the stirring is completed, sodium hydroxide aqueous solution is added to adjust the pH value to 11 to 12, and the mixture is allowed to stand for 10 hours to obtain a silica sol, and the silica sol is immersed in anhydrous ethanol for aging for 24 hours, and a silica gel is obtained after being taken out;
[0089] S2. First, mix Tween 60, silica gel and vegetable oil evenly according to the mass ratio of Tween 60: silica gel: vegetable oil: water = 4:40:80:100, then gradually add water and stir, control the system temperature at 55°C (temperature error is controlled within 2°C) during the water addition process, perform ultrasonic emulsification at a power of 500W for 20 minutes under heat preservation conditions to obtain silica emulsion;
[0090] S3, extracting the solids in the silica emulsion, washing the solids with water twice, and mixing the solids with water at a mass ratio of solids: water = 35: 100 to obtain an aqueous phase mixed solution including the silica core material;
[0091] S4, mixing Tween 60, kaolin, vegetable oil and water in a mass ratio of Tween 60: kaolin: vegetable oil: water = 6:25:50:100, raising the temperature to 68°C (temperature error controlled within 2°C) and performing ultrasonic emulsification for 20 minutes at a power of 500 W to obtain an oil phase mixed liquid including kaolin wall material;
[0092] S5. The oil phase mixture is added dropwise into the aqueous phase mixture containing Tween 60 at a mass ratio of Tween 60: oil phase mixture: aqueous phase mixture = 6:65:100. After the addition is completed, ultrasonic emulsification is performed at a power of 500 W for 20 minutes to separate the solids and prepare a composite inorganic filler.
[0093] S6. Mix the composite inorganic filler with hydroxyethyl acrylate and ethylene glycol dimethacrylate in a mass ratio of dibenzoyl peroxide: composite inorganic filler: hydroxyethyl acrylate: ethylene glycol dimethacrylate: polyethylene glycol = 0.2:40:100:100:150, add dibenzoyl peroxide and polyethylene glycol with a molecular weight of 500, raise the temperature to 78°C (the temperature error is controlled within 2°C), stir and react for 3 hours to obtain an anti-wear agent.
[0094] Performance Testing
[0095] The performance parameters of FDY crude oil type oil samples 1-5 are as follows:
[0096] Table 2
[0097] Among them, the test of oil film strength is carried out in accordance with GB / T3142. The dynamic friction coefficient and oiling rate are obtained by using FDY crude oil type oil sample 1-5 on the spinning position under the same conditions for 20 days. The spinning speed is 4800m / min and the GR2 temperature is 135℃. The detection method of smoke emission is to weigh 10 grams of sample and place it in a 50ml beaker, place the beaker in an electric heating sleeve for continuous heating, and observe its smoke emission. The detection method of coking property is to measure 1.0ml of sample and drop it on the steel sheet, place the steel sheet in an oven at 220℃ for heating treatment for 3min, and observe the coking performance of the sample after cooling to 25℃. The detection method of volatile reduction is to take 2 grams of sample and place it in a 50ml beaker, place the beaker in an oven at 200℃ for heating treatment for 2h, cool to 25℃, weigh and calculate the volatile amount of the sample. The detection method of open flash point is carried out in accordance with GB / T3536.
[0098] Although the present invention is disclosed as above, the present invention is not limited thereto. Any person skilled in the art can make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the protection scope of the present invention shall be subject to the scope defined by the claims.
Claims
1. A method for preparing an FDY crude oil type oil agent for polyester fiber, characterized in that: The preparation method comprises: S100, according to the mass ratio of sizing agent: antistatic agent: emulsifier: smoothing agent = (4-6): (5-8): (20-22): (55-60), the sizing agent, the antistatic agent, the emulsifier and the smoothing agent are added into a reaction kettle, stirring is started, the temperature is raised to 40° C. to 50° C. and stirring is continued for 20 min to 40 min to obtain a first mixture; S200, according to the mass ratio of triethanolamine: anti-wear agent: first mixture = (3-6): (10-15): 100, the triethanolamine and the anti-wear agent are put into the reactor and mixed with the first mixture, and the mixture is kept warm and stirred for 10 to 20 minutes to obtain the FDY crude oil type oil agent; The anti-wear agent is specifically prepared by the following steps: S311, mixing ethyl silicate with a mixture of ethanol and water, adding hydrochloric acid to adjust the pH value to 4 to 5, stirring and reacting for 2h to 3h, adding sodium hydroxide aqueous solution after the stirring to adjust the pH value to 11 to 12, standing for 10h to 12h to obtain silica sol, and immersing the silica sol in ethanol for aging for 24h to 36h, and taking it out to obtain silica gel; S312, firstly mix Tween 60, paraffin, the silica gel and carbon tetrachloride uniformly, then gradually add water and stir, control the system temperature to 50° C. to 60° C., and perform ultrasonic emulsification under heat preservation conditions to obtain a silica emulsion; S313, feeding the silica emulsion into a reactor, using carbon dioxide as a medium, supercritically extracting the liquid phase in the silica emulsion, after the supercritical extraction is completed, cooling and depressurizing, filtering and washing the solids, and mixing the solids and water uniformly to obtain an aqueous phase mixed liquid including the silica core material; S314, mixing Tween 60, kaolin, vegetable oil and water, raising the temperature to 65° C. to 70° C. and performing ultrasonic emulsification to obtain an oil phase mixed liquid including kaolin wall material; S315, adding the oil phase mixed solution dropwise into the water phase mixed solution containing Tween 60, and after the addition is completed, ultrasonic emulsification is performed evenly to separate the solid matter, thereby preparing a composite inorganic filler; S316, mixing the composite inorganic filler with hydroxyethyl acrylate and ethylene glycol dimethacrylate, adding dibenzoyl peroxide and polyethylene glycol with a molecular weight of 400 to 600, raising the temperature to 75° C. to 80° C. and stirring the reaction for 3 h to 3.5 h to obtain the wear-resistant agent.
2. The preparation method according to claim 1, characterized in that: The sizing agent includes at least one of lauroyl diethanolamine, coconut oleic acid diethanolamide, oleic acid triethanolamine, polyethylene glycol oleate, and polyethylene glycol laurate.
3. The preparation method according to claim 1, characterized in that: The antistatic agent includes at least one of lauryl alcohol polyoxyethylene ether potassium phosphate, secondary alkyl sodium sulfonate and lauryl alcohol polyoxyethylene ether.
4. The preparation method according to claim 1, characterized in that: The emulsifier includes at least one of isomeric alcohol polyoxyethylene ether, sorbitan fatty acid ester, polyethylene glycol fatty acid ester, castor oil polyoxyethylene ether, cardanol polyoxyethylene ether, and sodium lauryl ether sulfate.
5. The preparation method according to claim 1, characterized in that: The lubricant includes at least one of mineral oil, vegetable oil, silicone oil, and at least one of fatty alcohol oleate or polyol oleate.
6. The preparation method according to claim 1, characterized in that: Based on 100 parts by mass, the lubricant includes: 55 parts of mineral oil; 15 parts of polyol fatty acid ester; 10 parts of copolyether; 10 parts of phosphate ester; and 10 parts of silicon oxide.
7. The preparation method according to claim 1, characterized in that: The antistatic agent is prepared by the following steps: S110, dissolving chitosan in a 2% vol to 3% vol acetic acid aqueous solution to prepare a 4 wt % to 6 wt % chitosan aqueous solution; S120. According to the mass ratio of initiator: water-soluble acrylic acid monomer: isotridecyl alcohol polyoxyethylene ether: chitosan aqueous solution = (4-6): (60-80): (40-50): 100, the initiator, the isotridecyl alcohol polyoxyethylene ether and the chitosan aqueous solution are uniformly mixed, stirred uniformly at a temperature of 50°C to 55°C, heated to 75°C to 80°C, added with the water-soluble acrylic acid monomer, and continued stirring for 1h to 1.5h. After the stirring is completed, the mixture is cooled to room temperature to obtain the antistatic agent.
8. The preparation method according to claim 1, characterized in that: In S311, by mass ratio, ethyl silicate: ethanol: water = (6-10): (30-35): 100; In S312, by mass ratio, Tween 60: paraffin: silica gel: carbon tetrachloride: water = (4-8): (15-20): (30-40): 60: 100; In S313, the supercritical extraction is performed at a temperature of 30° C. to 33° C. and a pressure of 7.2 MPa to 7.5 MPa, based on mass ratio; In S314, by mass ratio, Tween 60: kaolin: vegetable oil: water = (4-8): (20-25): (40-50): 100; In S315, the mass ratio of Tween 60: oil phase mixture: water phase mixture = (4-8): (60-80): 100; In S316, the mass ratio of dibenzoyl peroxide:composite inorganic filler:hydroxyethyl acrylate:ethylene glycol dimethacrylate:polyethylene glycol = (0.2-0.3): (35-45): 100: 100:
150.
9. An FDY crude oil type oil agent for polyester fiber, characterized in that: The FDY crude oil type oil agent for polyester fiber is obtained by the preparation method as described in any one of claims 1 to 8.
Citation Information
Patent Citations
High-temperature oil agent for polyester industrial yarns, and preparation method thereof
CN111206427A
High-temperature-resistant spinning oil and preparation method thereof
CN117947635A